PENGARUH MODEL PEMBELAJARAN KOLABORATIF DENGAN TEKNIK THREE STEP INTERVIEW TERHADAP PRESTASI BELAJAR MATA PELAJARAN SEJARAH SISWA KELAS XI SMA NEGERI 1 SIGLI TAHUN AJARAN 2017/2018 - Arif Muttaqin; Anwar Yoesoef; Teuku Abdullah (Universitas Syiah Kuala, 2018)
ABSTRACTLearning model hightly affects the learning outcomes that a teacher wants to achieve. To obtain high student learning outcomes, one of the method is the application of collaborative learning model with three step interview technique. This study entitled